Night lights and regional income inequality in Africa - Anthony Mveyange (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Estimating regional income inequality in Africa has been challenging due to the lack of reliable and consistent sub-national income data. I employ night lights data to circumvent this limitation. I find significant and positive associations between regional inequality visible through night lights and income in Africa. Thus, in the absence of income data, we can construct regional inequality proxies using night lights data. Further investigation on the night lights-based regional inequality trends reveals two main findings: first, increasing regional inequality trends between 1992 and 2003; and second, declining regional inequality trends between 2004 and 2012.
Keywords: I132; R10; O55; 330; regional income inequality; night lights; Africa